Sex Determination by Odontometric Diagonal Measurements Using Discriminant Function - Gunjan V Moon; Ramhari S Sathawane; Rakhi M Chandak; Ashish B Lanjekar; Kshitia Bhakte; Vidyarjan A Sukhdeve (Wolters Kluwer Medknow Publications, 2021)
Introduction: Forensic odontology is one of the most unexplored and captivated branches of forensic sciences. Teeth are far excellent material for the anthropological, genetic, odontogenic, and forensic scenario as the morphology of teeth remains unchanged in extreme environmental conditions even after a long period. Aim and Objectives: The study aims to determine the sex of an individual by odontometric diagonal measurements using discriminant function. The objectives are to measure and compare the diagonal measurements of teeth in males and females using crown diagonal diameters of the permanent dentition and to evaluate their sexual dimorphism. Material and Methods: The study sample included 380 maxillary and mandibular dental casts obtained by alginate impressions of 190 subjects (95 males and 95 females) in the age range of 19-35 years selected from Out patient department of Oral Medicine and Radiology. Mesiolabioincisal-distolinguoincisal (MBDL) and distolabioincisal-mesiolinguoincisal (DBML) measurements of right permanent maxillary and mandibular teeth excluding third molars were taken separately using a digital Vernier caliper. Results: The highest mean tooth dimension of MBDL and DBML in both the jaws is of the first molar. The accuracy rate for males (100% for MBDL and 97.89% for DBML) is greater than females (MBDL 93.68% and DBML 94.21%). The overall accuracy rate of maxillary and mandibular MBDL is greater (96.8%) than DBML measurement (95.8% and 94.8%, respectively). Conclusion: The overall accuracy rate for sex determination is 96.8% for MBDL dimensions. The maxillary and mandibular second premolars are the strongest predictors for sex determination.